Serum netrin-1 and netrin receptor levels in fibromyalgia and osteoarthritis - Kohle, Alparslan; Gulkesen, Arif; Karatas, Tuba Kaya; Akgol, Gurkan; Karatas, Ahmet; Ilhan, Necip; Koca, Suleyman Serdar (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2022)
Objectives: This study aims to define serum levels of netrin-1 and netrin receptors in patients with fibromyalgia (FM) and osteoarthritis (OA). Patients and methods: This cross-sectional study was conducted with a total of 150 female participants (mean age: 47.2 +/- 16.1 years; range, 18 to 89 years) at F??rat University between June 2016 and December 2016. The participants were evaluated in three groups: the FM group with 50 patients, the OA group with 50 patients, and the control group, which included 50 healthy volunteers. Netrin-1, netrin receptors (DCC, UNC5B, and UNC5D), interleukin (IL)-6, IL-10, and IL-17 levels were analyzed by the enzyme-linked immunosorbent assay from the serum samples of the participants. Results: The level of serum netrin-1 was significantly lower in the FM group than in the control and OA groups (p<0.01 and p<0.001, respectively). However, the difference between patients with OA and healthy controls in terms of netrin-1 was not statistically significant (p>0.05). In addition, serum levels of netrin receptors and cytokines in the FM group were similar to the control group (p>0.05). However, serum DCC, UNC5D, IL-6, and IL-10 levels were higher in the OA group compared to the control group (p<0.001, p<0.05, p<0.01, and p<0.001, respectively). Conclusion: Serum netrin-1 level is suppressed in FM, which suggests that netrin-1 is influential in FM pathogenesis.
Keywords: Cytokine; fibromyalgia; netrin-1; osteoarthritis